Optimalisasi Penggunaan Media Sosial untuk Pemberdayaan Ibu-ibu di Desa Jati Indah Lampung Selatan - Yuli Syafitri; Reni Astika; Tsamariaty Hidayah; Deddy Sulaimawan; Irwandi Irwandi; Didi Susianto (Universitas Pahlawan Tuanku Tambusai, 2022)
The continuous development of technology and the changing concept of working from home makes people inevitably move to the world of digitalization. Optimizing the use of information technology is a mandatory step for the community to continue to survive and develop. This causes social media to evolve faster, as can be seen from community interactions that are no longer one-way but two-way without any obstacles. The counseling activity delivered material on wise use of smartphones for children's education, introduction of social media and its use, building and creating businesses in the era of digitalization, bookkeeping management and product marketing through social media and hoaxes. The method used is an outreach method with the target of mothers. The result of community service activities is the development of ideas, especially to improve the family economy by using social media as a forum to open up business opportunities and overcome hoax news on social media.